Pengaruh Dana Bagi Hasil, Dana Alokasi Umum, Dana Alokasi Khusus dan Pariwisata Terhadap Kemiskinan di Provinsi Daerah Istimewa Yogyakarta - Gala Perkasa Widyatama; Diah Setyorini Gunawan; Suharno Suharno (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Fiscal decentralization is a delegation of authority from the central government to regional governments in managing regional finances. The balancing fund is one of the funds in the context of implementing fiscal decentralization and can be used for poverty alleviation. DI Yogyakarta Province is a region that has a high balance of funds, however DI Yogyakarta Province is the province that has the highest number of poor people on the island of Java. This research is quantitative research using panel data. Data was obtained from the central statistical agency of five districts/cities in DI Yogyakarta Province. The analysis method uses panel data regression for 2009-2022 in five districts/cities. The results of the analysis show that general allocation funds and special allocation funds have a negative and significant effect on the poverty level in DI Yogyakarta. Meanwhile, profit sharing funds and tourism have no effect on the poverty level in DI Yogyakarta.